The mean value theorem for holomorphic functions - Radzievska, Elena (My University, 2013)
Was studied the problem of representing the remainder of the Taylor expansion for a holomorphic function in Lagrange form. Встановлюється можливість подання залишкового члена в ряді Тейлора для голоморфних функцій у формі Лагранжа
Keywords: mean value theorem; Remainder; holomorphic functions; Taylor expansion; теорема про середнє; залишковий член; голоморфна функція; Ряд Тейлора; теорема о середнем; остаточный член; голоморфная функция; кафедра вищої математики імені проф. Можара В. І.